2020
DOI: 10.1002/ett.4150
|View full text |Cite
|
Sign up to set email alerts
|

Network intrusion detection system: A systematic study of machine learning and deep learning approaches

Abstract: The rapid advances in the internet and communication fields have resulted in a huge increase in the network size and the corresponding data. As a result, many novel attacks are being generated and have posed challenges for network security to accurately detect intrusions. Furthermore, the presence of the intruders with the aim to launch various attacks within the network cannot be ignored. An intrusion detection system (IDS) is one such tool that prevents the network from possible intrusions by inspecting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
215
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 593 publications
(324 citation statements)
references
References 129 publications
1
215
0
3
Order By: Relevance
“…Deep learning (DL) is a subset of ML that consists of several hidden layers used to obtain the deep network's characteristics. Due to their deep structure and ability to learn the important features from the dataset on their own and produce an output, these techniques are more effective than ML [24].…”
Section: Related Workmentioning
confidence: 99%
“…Deep learning (DL) is a subset of ML that consists of several hidden layers used to obtain the deep network's characteristics. Due to their deep structure and ability to learn the important features from the dataset on their own and produce an output, these techniques are more effective than ML [24].…”
Section: Related Workmentioning
confidence: 99%
“…Ahamed et al 21 present an elaborate study of various Machine learning and Deep learning methodologies in the process of designing NIDS. This study article highlights the merits and challenges faced by various methodologies while detecting the attacks.…”
Section: Related Workmentioning
confidence: 99%
“…The usage of old datasets for network security research is notorious [9], being challenging to tackle this issue, as described in [6]. The use of old datasets on NIDS research stills a concern as confirmed by [10]- [13], which reports the adoption of DARPA 1998, KDD-CUP '99, and NSL-KDD as the most-used ones, yet these datasets are around two decades old by now. An important factor in favor of reusing old datasets is applying Machine Learning (ML) algorithms to provide new approaches.…”
Section: B Machine Learning (Ml) On Nids Domainmentioning
confidence: 99%
“…Content may change prior to final publication. [10] ML and DL [11] ML and DL [12] Datasets [13] ML and DL [14] Datasets [15] Methods [16] IoT AB-TRAP ML and Datasets and being a promising hybrid approach, the authors do not present the realization and performance evaluation of the solution to confirm their claims. It is also dependent on others datasets to continually evolve its solution.…”
Section: B Machine Learning (Ml) On Nids Domainmentioning
confidence: 99%